Organic-inorganic composite light nano fireproof fiber and preparation method thereof
By introducing silver nanoparticles on the surface of polyimide nanofibers to form a silver cladding layer, the problems of low electrostatic effect and mechanical strength of the fiber are solved, and higher high temperature resistance and flame retardant properties are achieved.
Patent Information
- Application Number
- CN202411838240.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The existing polyimide-based nanofibers have severe electrostatic effects during spinning and have low mechanical strength, making it difficult to meet the strength and temperature resistance requirements of fire-fighting fabrics.
By introducing silver nanoparticles on the surface of polyimide nanofibers in redox manner, a silver cladding layer is formed, which reduces the electrostatic effect of the nanofibers and enhances the mechanical properties.
It effectively alleviates the electrostatic effect of nanofibers, improves its mechanical strength and high temperature resistance, and improves the spinning and flame retardant properties of the fibers.
Smart Images

Figure HDA0005187314110000011 
Figure HDA0005187314110000012 
Figure HDA0005187314110000021
Abstract
Description
Technical Field
[0001] The invention relates to the field of fire prevention and flame retardancy, and in particular to an organic-inorganic composite lightweight nano fireproof fiber. Background Art
[0002] Fire-retardant materials are a type of material that can slow down or organize the combustion process, improve the temperature resistance of materials, slow down the burning rate or prevent combustion. When these materials are attacked by external fire sources, they can slow down or prevent the spread of flames, thereby achieving the purpose of flame retardancy. At present, fire-retardant materials are widely used in firefighting, construction, electronic appliances, medical treatment and even aerospace, especially in firefighting clothing, which can provide important protection for firefighters in extreme fire environments. At present, fire-retardant materials generally have poor physical properties such as strength and toughness, and because of the addition of halogens, a large amount of smoke and hydrogen chloride gas will be released during combustion. These smoke and gases will irritate people's eyes and respiratory tracts and hinder firefighting and rescue work. Polyimide fiber has extremely high thermal stability, and its glass transition temperature is usually above 300°C. Its smoke rate is low, and less smoke is generated during combustion. It is basically non-toxic and has good flame retardant effect. It is widely used in firefighting clothing. However, due to the high resistance of polyimide, there is a serious electrostatic effect during the spinning process and it is difficult to eliminate, which increases the difficulty of its related applications as a fabric; at the same time, as a fire-fighting fabric, its material strength and temperature resistance need to be further strengthened.
[0003] Prior art "Study on Preparation of Polyimide Nanofibers by Electrospinning - Bu Chengcheng" describes in detail the process of preparing polyimide nanofibers by electrospinning, including using polyamic acid as a precursor, thermal cyclization and other steps. This goal is achieved through doping compounding. However, the doping compounding method has obvious limitations, such as the existence of a doping threshold that prevents the doping concentration from increasing indefinitely, and the difficulty of evenly dispersing the introduced medium in polyamic acid, which may cause clogging of the electrospinning needle or uneven thickness of the nanofibers.
[0004] "Size Effect of Nanosilver Enhanced Regenerated Fiber Mechanical Properties - Guo Jianjun" introduces the introduction of silver nanoparticles on the surface of polyimide nanofibers to form a stable silver coating, thereby significantly enhancing the mechanical properties of the fibers. For example, hybrid fibers containing 2nm silver nanoparticles exhibit excellent mechanical properties, with a fracture strain of 138.27%, far exceeding that of blank fibers. The method of directly adding silver nanoparticles to the silk fibroin electrospinning solution for spinning and directly introducing them into RSF has the above-mentioned problems of doping threshold, needle clogging, and uneven thickness of electrospun fibers, and may also reduce the molecular weight of the silk fibroin electrospinning solution, resulting in the inability to carry out the electrospinning process.
[0005] "In-situ preparation of polyimide / nanosilver ultrafine composite fibers - Zhang Qian" A method for preparing polyimide / nanosilver composite fibers by electrospinning. This method uses silver trifluoroacetylacetonate (AgTFA) as a silver salt matrix. After electrospinning and subsequent heat treatment, the silver ions are reduced to elemental silver and evenly distributed in the polyimide fibers. Although this is also an effective method for introducing elemental silver, and in addition to silver trifluoroacetylacetonate, more easily accessible silver acetate can also be introduced, this method also has the above-mentioned doping threshold limitation and the problem of elemental silver being easily oxidized during heating. Summary of the invention
[0006] In order to overcome the shortcomings of existing polyimide-based nanofibers, such as serious electrostatic phenomena and low mechanical strength, this technical solution provides an organic-inorganic composite lightweight nano fireproof fiber and a preparation method, which introduces silver nanoparticles on the surface of polyimide nanofibers in an oxidation-reduction manner to form a silver coating layer, thereby achieving the purpose of reducing the electrostatic effect of nanofibers and enhancing mechanical properties. This in-situ reduction method avoids the doping threshold and uneven fiber size problems in the traditional process of introducing silver elements. The silver content on the fiber surface can be arbitrarily adjusted according to the use requirements and silver-coated nanofibers of uniform size can be obtained. The fire-retardant fiber prepared from the fiber not only has an effective alleviation of the electrostatic effect, but also has enhanced mechanical strength and high temperature resistance.
[0007] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0008] The present invention provides a method for preparing an organic-inorganic composite lightweight nano fireproof fiber, comprising the following steps:
[0009] Step 1, add 0.00255 mol of 4,4'-diaminodiphenyl ether and 7 ml of N,N'-dimethylacetamide into a two-necked bottle, stir thoroughly to dissolve, then add a certain molar ratio of pyromellitic anhydride into the solution four times, stir for 6 hours to obtain a yellow viscous polyamic acid solution;
[0010] Step 2, electrospinning the yellow viscous solution by electrospinning technology to obtain a polyimide nanofiber film. The film is removed and dried in a vacuum drying oven to remove the organic solvent in the fiber. Then, the nanofiber film is subjected to high-temperature heat treatment in a muffle furnace to obtain a formed polyimide film;
[0011] Step 3, placing the polyimide film in a sodium hydroxide solution for 30 seconds, then placing it in a mixed solution of hydrochloric acid and stannous chloride and stirring it for 10 minutes, taking out the film and then placing it in a silver nitrate solution and stirring it for 30 minutes, finally adding ethanol and formaldehyde to the silver nitrate solution, and after standing for 48 hours, an organic-inorganic composite polyimide-based fireproof material is obtained.
[0012] In the above scheme, in step 1, the reaction in step 1 is carried out in a nitrogen atmosphere, and the reaction temperature should be maintained at 0°C.
[0013] In the above scheme, the molar ratio of pyromellitic anhydride to 4,4'-diaminodiphenyl ether in step 1 is 1:1.03.
[0014] In the above scheme, in step 2, the high voltage power supply voltage is 16KV, the electrospinning flow rate is 0.4mL / h, and the distance of the needle collection device is 16cm.
[0015] In the above scheme, the imidization temperature in step 2 is 300°C.
[0016] In the above scheme, in step 3, the concentration of sodium hydroxide solution is 10 g / L, the concentrations of hydrochloric acid and stannous chloride are 0.01 mol / L and 20 g / L respectively, the concentration of silver nitrate is 5 g / L, and the contents of ethanol and formaldehyde are 10 ml and 2 ml respectively.
[0017] In the above scheme, when replacing the solution in step 3, it is necessary to wash with deionized water three times.
[0018] The present invention also provides an organic-inorganic composite light-weight nano-fireproof fiber obtained by the organic-inorganic composite light-weight nano-fireproof fiber and the preparation method thereof.
[0019] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0020] 1. The preparation method of the present invention has a reasonable structural design, rich material sources, and a simple process. The silver nanoparticle coating method reduces the electrostatic effect of the polyimide nanofiber and improves the spinnability of the polyimide nanofiber as a fabric. At the same time, the silver nanoparticles are coated on the surface of the polyimide fiber, which has a certain enhancement effect on its mechanical properties.
[0021] 2. The technical solution of the present invention fills the technical gap in the industry at home and abroad: the current fire-retardant materials generally have poor physical properties such as strength and toughness, and because of the halogens added therein, a large amount of smoke and hydrogen chloride gas will be released during combustion. These smoke and gases will irritate people's eyes and respiratory tract, hindering firefighting and rescue work. The preparation method of organic-inorganic composite lightweight nano fireproof fiber is used to attach silver nanoparticles to the surface of polyimide fiber. Not only does the electrostatic induction on the surface of the nanofibers be reduced or even eliminated by the conductive silver nanoparticles, which greatly enhances its spinnability and heat-resistant flame-retardant properties, but polyimide will not produce toxic gases during the heating process, which plays a positive protective role in firefighting work; and the method of in-situ reduction of silver element is used to avoid the problem of doping threshold when directly introducing doping media into the electrospinning matrix, and nanofibers of uniform size with different silver contents can be obtained according to demand.
[0022] Third, the technical solution of the present invention overcomes technical prejudice: the fireproof fiber synthesized from high-performance organic matter often has a more serious surface electrostatic effect due to the ultra-high resistance of the polymer material, which greatly increases the various costs of this type of material in the textile process. We deposited silver nanoparticles on the surface of polymer polyimide nanofibers to make organic-inorganic composite lightweight nano fireproof fibers, which reduced or even eliminated the electrostatic induction on the surface of the nanofibers and greatly enhanced the spinnability of the polyimide fibers. At the same time, the introduction of silver nanoparticles has a certain improvement in the temperature resistance and mechanical strength of the nanofibers. In addition, by the method of in-situ reduction of silver element, not only can the content of the introduced inorganic medium be arbitrarily regulated and the restriction of the doping threshold be removed, but also the uniformity of the nanofibers will not be affected during the electrospinning process, and the oxidation problem of elemental silver in the preparation process is avoided. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 This is a flow chart of an organic-inorganic composite lightweight nano fireproof fiber and a preparation method provided by an embodiment of the present invention;
[0025] Figure 2 is a SEM picture of the nanofibers obtained in Example 1 of the present invention before and after compounding;
[0026] Figure 3 is the XRD diagram of the nanofiber obtained in Example 1 of the present invention before and after compounding;
[0027] Figure 4 is a thermogravimetric diagram of the composite nanofibers obtained in Example 1 of the present invention;
[0028] Figure 5 is a graph of mechanical properties of the nanofibers obtained in Example 1 of the present invention before composite;
[0029] Figure 6 This is a graph showing the mechanical properties of the nanofibers obtained in Example 1 of the present invention after being heat treated at 400° C. before being composited;
[0030] Figure 7 This is a graph showing the mechanical properties of the composite nanofibers obtained in Example 1 of the present invention;
[0031] Figure 8 This is a diagram of the mechanical properties of the nanofibers obtained in Example 1 of the present invention after being composited and heat treated at 400°C. DETAILED DESCRIPTION
[0032] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.
[0033] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.
[0034] In order to prove the creativity and technical value of the technical solution of the present invention, this section provides application examples of the claimed technical solution on specific products or related technologies.
[0035] The present invention provides an ultra-sensitive electronic skin based on a microporous structure and a preparation method thereof, comprising the following steps:
[0036] Step 1, add 0.00255 mol of 4,4'-diaminodiphenyl ether and 7 ml of N,N'-dimethylacetamide into a two-necked bottle, stir thoroughly to dissolve, then add a certain molar ratio of pyromellitic anhydride into the solution four times, stir for 6 hours to obtain a yellow viscous polyamic acid solution;
[0037] Step 2, electrospinning the yellow viscous solution by electrospinning technology to obtain a polyimide nanofiber film. The film is removed and dried in a vacuum drying oven to remove the organic solvent in the fiber. Then, the nanofiber film is subjected to high-temperature heat treatment in a muffle furnace to obtain a formed polyimide film;
[0038] Step 3, placing the polyimide film in a sodium hydroxide solution for 30 seconds, then placing it in a mixed solution of hydrochloric acid and stannous chloride and stirring it for 10 minutes, taking out the film and then placing it in a silver nitrate solution and stirring it for 30 minutes, finally adding ethanol and formaldehyde to the silver nitrate solution, and after standing for 48 hours, an organic-inorganic composite polyimide-based fireproof material is obtained.
[0039] Example 1
[0040] The present invention provides an organic-inorganic composite lightweight nano fireproof fiber and a preparation method thereof, comprising the following steps:
[0041] Step 1, add 0.00255 mol of 4,4'-diaminodiphenyl ether and 7 ml of N,N'-dimethylacetamide into a two-necked bottle, stir thoroughly to dissolve, then add a certain molar ratio of pyromellitic anhydride into the solution four times, stir for 6 hours to obtain a yellow viscous polyamic acid solution;
[0042] Step 2, electrospinning the yellow viscous solution by electrospinning technology to obtain a polyimide nanofiber film. The film is removed and dried in a vacuum drying oven to remove the organic solvent in the fiber. Then, the nanofiber film is subjected to high-temperature heat treatment in a muffle furnace to obtain a formed polyimide film;
[0043] Step 3, placing the polyimide film in a sodium hydroxide solution for 30 seconds, then placing it in a mixed solution of hydrochloric acid and stannous chloride and stirring it for 10 minutes, taking out the film and then placing it in a silver nitrate solution and stirring it for 30 minutes, finally adding ethanol and formaldehyde to the silver nitrate solution, and after standing for 48 hours, an organic-inorganic composite polyimide-based fireproof material is obtained.
[0044] In the above scheme, in step 1, the reaction in step 1 is carried out in a nitrogen atmosphere, and the reaction temperature should be maintained at 0°C.
[0045] In the above scheme, the molar ratio of pyromellitic anhydride to 4,4'-diaminodiphenyl ether in step 1 is 1:1.03.
[0046] In the above scheme, in step 2, the high voltage power supply voltage is 16KV, the electrospinning flow rate is 0.4mL / h, and the distance of the needle collection device is 16cm.
[0047] In the above scheme, the imidization temperature in step 2 is 300°C.
[0048] In the above scheme, in step 3, the concentration of sodium hydroxide solution is 10 g / L, the concentrations of hydrochloric acid and stannous chloride are 0.01 mol / L and 20 g / L respectively, the concentration of silver nitrate is 5 g / L, and the contents of ethanol and formaldehyde are 10 ml and 2 ml respectively.
[0049] The electronic skin prepared by the organic-inorganic composite lightweight nano fireproof fiber and the preparation method provided in the embodiment of the present invention can be applied to the fields of aerospace, electronics, medical treatment, fire protection, etc. The embodiment of the present invention has achieved some positive effects in the process of research and development or use, and it does have great advantages compared with the existing technology. The following content is described in combination with the data, icons, etc. of the test process.
[0050] The organic-inorganic composite lightweight nano fireproof fiber prepared in Example 1 is applied in the field of fire safety. Figure 2 The figure shows the comparison of the XRD spectrum of the composite fiber prepared in Example 1 with the standard card. The peaks (111), (200), (220) and (311) all correspond to the standard card, proving that the silver nanoparticles have been successfully attached to the surface of the nanofibers. Figure 3 It can be observed that the nanofibers obtained by electrospinning technology have uniform diameters and no obvious beads. The diameter of the nanofibers is about 300nm. Figure 3 In (b), silver nanoparticles attached to the surface of the nanofibers can be clearly observed. The particles are neatly arranged and evenly attached to the fiber surface. The particle diameter is about 50 nm. Figure 4 As shown in the figure, the water of organic-inorganic composite nanofibers evaporates below 300℃, resulting in a decrease in mass. Between 300℃ and 500℃, the mass increases. This is because the test environment is an atmospheric environment. Under high temperature conditions, silver is oxidized to silver oxide, resulting in an increase in mass. After 500℃, the mass of the composite nanofibers begins to decrease, indicating that the nanofibers begin to pyrolyze at high temperatures at this time. Through silver coating treatment, the high temperature resistance of polyimide nanofibers can be increased to 500℃. At the same time, Figure 5-8 We found that the initial nanofiber breaking strength was 17.8Mpa, and after high-temperature treatment at 400℃, the nanofiber breaking strength dropped to 9.16Mpa. The nanofiber obtained by organic-inorganic composite had a breaking strength of up to 21.44Mpa. Even after high-temperature treatment at 400℃, its breaking strength was still as high as 15.34Mpa, indicating that the nanofiber obtained by organic-inorganic composite not only has improved high-temperature resistance, but also has improved fiber strength; and silver nanoparticles as conductive ions can effectively reduce the electrostatic effect on the fiber surface. These effects make this organic-inorganic composite nanofiber widely used in the field of fire safety.
Claims
1. A method for preparing an organic-inorganic composite lightweight nano fireproof fiber, characterized in that: The following steps are involved: Step 1, add 0.00255 mol of 4,4'-diaminodiphenyl ether and 7 ml of N,N'-dimethylacetamide into a two-necked bottle, stir thoroughly to dissolve, then add pyromellitic anhydride four times, stir for 6 hours to obtain a yellow viscous polyamic acid solution; Step 2, electrospinning the polyamic acid solution by electrospinning technology to obtain a polyimide nanofiber film, removing the film and drying it in a vacuum drying oven to remove the organic solvent in the fiber, and then subjecting the nanofiber film to high-temperature heat treatment in a muffle furnace to obtain a formed polyimide film; Step 3, placing the polyimide film in a sodium hydroxide solution, a mixed solution of hydrochloric acid and stannous chloride, and a silver nitrate solution in turn for treatment, and finally adding ethanol and formaldehyde to the silver nitrate solution, and then standing to obtain an organic-inorganic composite polyimide-based fireproof material.
2. The method for preparing an organic-inorganic composite lightweight nano fireproof fiber according to claim 1, characterized in that: The reaction in step 1 is carried out in a nitrogen atmosphere, and the reaction temperature should be maintained at 0°C.
3. The method for preparing an organic-inorganic composite lightweight nano fireproof fiber according to claim 1, characterized in that: In the step 1, the molar ratio of pyromellitic anhydride to 4,4'-diaminodiphenyl ether is 1:1.
03.
4. The method for preparing an organic-inorganic composite lightweight nano fireproof fiber according to claim 1, characterized in that: In step 2, the voltage of the high voltage power supply is 16 KV, the electrospinning flow rate is 0.4 mL / h, and the distance of the needle collection device is 16 cm.
5. The method for preparing an organic-inorganic composite lightweight nano fireproof fiber according to claim 1, characterized in that: The imidization temperature in step 2 is 300°C.
6. The method for preparing an organic-inorganic composite lightweight nano fireproof fiber according to claim 1, characterized in that: In step 3, the concentration of the sodium hydroxide solution is 10 g / L, the concentrations of hydrochloric acid and stannous chloride are 0.01 mol / L and 20 g / L respectively, the concentration of silver nitrate is 5 g / L, and the contents of ethanol and formaldehyde are 10 ml and 2 ml respectively.
7. The method for preparing an organic-inorganic composite lightweight nano fireproof fiber according to claim 1, characterized in that: When replacing the solution in step 3, the solution needs to be washed with deionized water three times.
8. An organic-inorganic composite lightweight nano fireproof fiber, characterized in that: The preparation method is described in any one of claims 1 to 7.
Citation Information
Patent Citations
Cerium dioxide coated polyimide composite nanofiber membrane and preparation method thereof
CN113897775A
Heat-conducting filler / polyimide aerogel metallized high-heat-conductivity composite material and preparation method thereof
CN115850788A